Reactome: a knowledge base of biologic pathways and processes - Vastrik, Imre; D'Eustachio, Peter; Schmidt, Esther; Joshi-Tope, Geeta; Gopinath, Gopal; Croft, David; de Bono, Bernard; Gillespie, Marc; Jassal, Bijay; Lewis, Suzanna; Matthews, Lisa; Wu, Guanming; et al. (Genome biology, 2007)
Reactome http://www.reactome.org , an online curated resource for human pathway data, provides infrastructure for computation across the biologic reaction network. We use Reactome to infer equivalent reactions in multiple nonhuman species, and present data on the reliability of these inferred reactions for the distantly related eukaryote Saccharomyces cerevisiae . Finally, we describe the use of Reactome both as a learning resource and as a computational tool to aid in the interpretation of microarrays and similar large-scale datasets.